A Demonstration of Mokken Scale Analysis Methods Applied to Cognitive Test Validation Using the Egyptian WAIS-IV. (July 2020) - Abdelhamid, Gomaa S. M.; Gómez-Benito, Juana; Abdeltawwab, Ahmed T. M.; Abu Bakr, Mostafa H. S.; Kazem, Amina M.
The fourth edition of the Wechsler Adult Intelligence Scale (WAIS-IV) has been used extensively for assessing adult intelligence. This study uses Mokken scale analysis to investigate the psychometric proprieties of WAIS-IV subtests adapted for the Egyptian population in a sample of 250 adults between 18 and 25 years of age. The monotone homogeneity model and the double monotonicity model were consistent with the subtest data. The items of all subtests except Matrix Reasoning, Information, Similarities, and Vocabulary formed a unidimensional scale. The WAIS-IV subtests have discriminatory and invariantly ordered items, although some items violated the invariant item ordering and scalability criteria. Therefore, the WAIS-IV subtests—with the exception of some items—are hierarchical scales that allow items to be ordered according to difficulty and subjects to be ordered using the sum score. In conclusion, the current study provides evidence of the dimensionality and hierarchy of the WAIS-IV subtests in the framework of Mokken scaling, although care should be taken when interpreting or including certain items.